(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The absence of teeth leads to dysfunction of the gastrointestinal tract, speech function. At an older age (13-15 years old), children become less contact, withdrawn and laugh little. All this ultimately leads to various nervous disorders. On the basis of experimental and clinical observations, it was established that disruption of the continuity of the dentition causes pathomorphological and functional changes near the defect and extends to the entire dentition, and then to the entire body as a whole.